2005
DOI: 10.1159/000084181
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Adipocyte-Derived Leucine Aminopeptidase via Angiotensin II in Endometrial Carcinoma

Abstract: Objective: It has recently been appreciated that a local autocrine or paracrine renin-angiotensin system (RAS) may exist in a number of tissues. Angiotensin II (AngII) is a potent RAS-derived vasoconstrictor peptide, and it is involved in tumor angiogenesis. We have cloned human adipocyte-derived leucine aminopeptidase (A-LAP), which degrades Ang II. This study investigated whether the expression of A-LAP, Ang II, angiotensin type I receptor (AT1R) and vascular endothelial growth factor (VEGF) correlates with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 29 publications
0
32
0
3
Order By: Relevance
“…Based upon measurements of ATII and ACE in fresh surgical specimens of pancreatic carcinoma, Ohta et al suggest that ATII is produced at significant levels in this form of carcinoma by an ACEindependent mechanism [195]. In a retrospective immunohistochemical study of endometrial carcinomas, Shibata et al found that ATII and AT1 expression were correlated with a significantly worse prognosis [196]. Interestingly, expression of adipocyte-derived leucine aminopeptidase, which degrades ATII, was inversely correlated with prognosis [196].…”
Section: Ras/bk In Cancer Angiogenesismentioning
confidence: 99%
“…Based upon measurements of ATII and ACE in fresh surgical specimens of pancreatic carcinoma, Ohta et al suggest that ATII is produced at significant levels in this form of carcinoma by an ACEindependent mechanism [195]. In a retrospective immunohistochemical study of endometrial carcinomas, Shibata et al found that ATII and AT1 expression were correlated with a significantly worse prognosis [196]. Interestingly, expression of adipocyte-derived leucine aminopeptidase, which degrades ATII, was inversely correlated with prognosis [196].…”
Section: Ras/bk In Cancer Angiogenesismentioning
confidence: 99%
“…In mammals, LAP3 is exopeptidase which can catalyze the peptide substrates or the amino termini of protein hydrolysis [8]. Altered LAP3 expression pattern and/or catalytic function could induce the peptide activation change, the cell cycle progression change in gynecologic malignancy [11,18], could adjust the insulin receptor of diabetic patients [19,20]. Recently, it has shown that LAP3 is overexpressed at human esophageal squamous cell carcinoma and could regulate proliferative and migration of esophageal squamous cell [21].…”
Section: Introductionmentioning
confidence: 99%
“…Имеются данные, что РАС вовлечена в злокачественную трансформацию и опухолевую прогрессию при некоторых видах гинекологического рака [53]. При раке эндометрия в образцах опухолевых тканей экспрессия АТ1Р и АII обнаруживалась параллельно с гиперэкспрессией VEGF; экспрессия АТ1Р и АII имела положительную корреляцию со снижением выживаемости пациентов и без признаков рака эндометрия [61][62]. Данные, касающиеся опухолей яичников, показывают, что повышенная экспрессия АТ1Р сопутствует переходу пограничной формы цистаденомы в инвазивную злокачественную форму и положительно коррелирует с экспрессией VEGF и плотностью микрососудов в опухолевой ткани яичников, а также со снижением выживаемости пациентов [63][64].…”
Section: изучение роли апф при плоскоклеточной карциноме шейки маткиunclassified